(2x-8x)-X=

Simple and best practice solution for (2x-8x)-X= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-8x)-X= equation:


Simplifying
(2x + -8x) + -1X = 0

Combine like terms: 2x + -8x = -6x
(-6x) + -1X = 0
(-6x) + -1X = 0

Reorder the terms:
-1X + (-6x) = 0

Solving
-1X + (-6x) = 0

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '(6x)' to each side of the equation.
-1X + (-6x) + (6x) = 0 + (6x)

Combine like terms: (-6x) + (6x) = 0
-1X + 0 = 0 + (6x)
-1X = 0 + (6x)
Remove the zero:
-1X = (6x)

Divide each side by '-1'.
X = (-6x)

Simplifying
X = (-6x)

See similar equations:

| X^5-5x^3+5=0 | | 14+x-27x-3x=-19-2x | | X-0.4=5.2 | | 4x+2-(x-3)=0 | | 3(2a-1)=5 | | 4(5y-2)= | | 3x/4+1/2=1/4 | | 2(3a+1)=7 | | 3d-4-5d=7+d | | 8(3x+2)-4x=6 | | 8x+42b+544z=1000 | | 8x+2y=242 | | (2,8)5/2= | | 3a-(4b+2a)+5b= | | 3x^5-12x^4-45x^3+180x^2-48x+192=0 | | A=sw+w*w | | 5x-7+3x=7x-10 | | 5j+10=5 | | (9x^2+8x-2)+(-5x^2-7x+3)= | | 10x-5=12+6x | | P+0.02p=142.8 | | 25(xsqured-9)=25(x-3)(x+3) | | 8(3n+5)=8(9n+9)+6 | | In(x)=20 | | x+x*0.14=500 | | C=a+(n-8)dforn | | -6x-1=-6 | | 42/0.5= | | 2a+7=5a+9 | | 10r^2-2r=-4r+6 | | (x-6)*(x-6)=(x*x)-396 | | 45=2y |

Equations solver categories